Rediseño e implementación de un medidor del tiempo de reacción humana - Montero, Y. (2009)
This article shows the redesign and implementation of a device that can demonstrate that, the time it takes a person making a decision is directly proportional to the number of alternatives that he or she has (Hick's Law), for which we have used the 16F876A microcontroller to govern a system that lets us capture the time it takes a person reacting to a light stimulus and then use that data to plot a graph (number of alternatives vs. reaction time) with aid of the program HUMAN REACTION TIME created in the Visual Basic programming language that facilitates the assessment and analysis of the results.